(NmESTOROVDENIQ PODZEMNYH WOD GORNO(B-(NSKLAD^ATYH OBLASTEJ NA PRIMERE pRIBAJKALXQ I zAPADNOGO zABAJKALXQ (B/s - (NbORISENKO(B, (NiWAN mIHAJLOWI^s; (NaDU[INOW(B, (NaLXBERT aLEKSEEWI^s; (NlITWINENKO(B, (NtATXQNA eWGENXEWNAs; (NpISARSKIJ(B, (Nb(B.(Ni(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 119-122 (87 (NNAZW(B.)s
(Nan sssr(B. (NsIB(B. (NOTD(B-(NNIE(B. (NbURQT(B. (NFIL(B., (NgEOL(B. (NIN(B-(NTs
Keywords: (NwODY PODZEMNYEs; (NzABAJKALXE zAPADNOEs; (NpRIBAJKALXEs